Chapter 6 Ageing and Gender Preferences in Rural Indonesia - kreager, philip (ISEAS Publishing, 2015)
This chapter draws on the longitudinal ethnographic and demographic field study of three communities representing major Indonesian ethnicities (Javanese, Sundanese, and Minangkabau), located in three of the five provinces that, since 1990, have reported more than 7 per cent of the population over the age of 60. Comparative ethnographic study supported by panel surveys enables us to establish contexts and variations in family and community support for older people, and the advantages and disadvantages that may accrue in consequence to older men and women. Similar patterns of socio-economic stratification exist in the three communities, which have an important bearing on elderly well-being, notably by influencing the supply of children, family network size and structure, and intergenerational exchanges. Following a brief introduction, in which the communities and research methodology are described, the chapter notes two contrasting preference structures that differentiate gender in the communities. Gender has a marked structural significance in matrilineal societies, like the Minangkabau, that is not manifest for the Javanese and Sundanese. Case studies then illustrate some aspects of these structures. The chapter concludes with a brief look to the future, by considering the expectations of current working age generations about their own later lives, and the limitations of relying exclusively on aggregate data to assess their likely policy needs.